Multilayer electronic assembly and method of manufacturing the same

CN114551102BActive Publication Date: 2026-10-27SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111319223.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-19
Filing Date
2021-11-09
Publication Date
2026-10-27
Estimated Expiration
2041-11-09

AI Technical Summary

Technical Problem

[0006]然而,随着内电极和介电层变得更薄,内电极连接度可能劣化,并且平滑度可能减小,因此可靠性可能劣化

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114551102B_ABST
    Figure CN114551102B_ABST
Patent Text Reader

Abstract

The present disclosure provides a multilayer electronic component and a manufacturing method thereof. The multilayer electronic component includes a main body including a dielectric layer and internal electrodes alternately disposed with the dielectric layer, and an external electrode disposed on the main body and connected to the internal electrodes. A composite layer including Sn and Ni is disposed at an interface between the internal electrode and the dielectric layer. The internal electrode includes a central portion and an interface portion between the composite layer and the central portion of the internal electrode. The interface portion includes a ceramic additive.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2020-0155173, filed on November 19, 2020, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field

[0002] This disclosure relates to a multilayer electronic component and a method for manufacturing the same. Background Technology

[0003] Multilayer ceramic capacitors (MLCCs) are chip capacitors mounted on printed circuit boards of various types of electronic products, including image display devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, mobile phones, etc., for charging or discharging.

[0004] Multilayer ceramic capacitors are used as components in a variety of electronic devices due to their advantages such as miniaturization, high capacitance, and ease of installation. In recent years, with the miniaturization of electronic devices such as computers and mobile devices, the demand for miniaturization and achieving high capacitance in multilayer ceramic capacitors has also increased.

[0005] To achieve miniaturization and high capacitance in multilayer ceramic capacitors, techniques are needed to reduce the thickness of the internal electrodes and dielectric layers.

[0006] However, as the internal electrode and dielectric layer become thinner, the internal electrode connectivity may deteriorate, and the smoothness may decrease, thus potentially reducing reliability. Summary of the Invention

[0007] One aspect of this disclosure is to improve the reliability of multilayer electronic components.

[0008] One aspect of this disclosure is to improve the electrode connectivity of the internal electrode.

[0009] One aspect of this disclosure is to increase the smoothness of the internal electrode.

[0010] Another aspect of this disclosure is to provide a multilayer electronic component with high reliability, small size and high capacitance.

[0011] However, the purpose of this disclosure is not limited to the above description, and will be more readily understood in the process of describing specific embodiments of this disclosure.

[0012] According to one aspect of this disclosure, a multilayer electronic component may include: a body including a dielectric layer and an inner electrode alternately disposed with respect to the dielectric layer; and an outer electrode disposed on the body and connected to the inner electrode. A composite layer comprising Sn and Ni may be disposed at the interface between the inner electrode and the dielectric layer, the inner electrode including a central portion and an interface portion between the composite layer and the central portion of the inner electrode. The interface portion may include a ceramic additive.

[0013] According to one aspect of this disclosure, a method of manufacturing a multilayer electronic component includes the following operations: preparing a ceramic green sheet; applying a paste for an inner electrode to the ceramic green sheet to form an inner electrode pattern; stacking the ceramic green sheet with the inner electrode pattern to form a laminate; first firing the laminate; second firing the first-fired laminate; sintering the second-fired laminate to form a body including a dielectric layer and an inner electrode; and forming an outer electrode on the body. The paste for the inner electrode may comprise Sn powder particles, ceramic additives, and conductive powder particles. The conductive powder particles may have a core-shell structure. The core comprises Ni, and the shell may comprise Ni, S, and O.

[0014] According to one aspect of this disclosure, a multilayer electronic component may include: a body including a dielectric layer and inner electrodes alternately disposed with respect to the dielectric layer; and an outer electrode disposed on the body and connected to the inner electrodes. The inner electrode may include a central portion and an interface portion spaced apart from the dielectric layer and including a ceramic additive, the interface portion being disposed between the dielectric layer and the central portion of the inner electrode. The area % of the ceramic additive in the interface portion may be greater than the area % of the ceramic additive in the central portion of the inner electrode. Attached Figure Description

[0015] The above and other aspects, features and advantages of this disclosure will be more clearly understood by taking into account the accompanying drawings and the following detailed description, in which:

[0016] Figure 1 A perspective view of a multilayer electronic assembly according to an embodiment of the present disclosure is shown schematically;

[0017] Figure 2 Schematic illustration along Figure 1 A cross-sectional view taken from line I-I';

[0018] Figure 3 Schematic illustration along Figure 1 A cross-sectional view taken from line II-II';

[0019] Figure 4 This is an exploded perspective view schematically showing a body having a stacked dielectric layer and internal electrodes according to an embodiment of the present disclosure;

[0020] Figure 5 It is shown Figure 2 A magnified view of region P1;

[0021] Figure 6 It is shown Figure 5 A magnified view of region P2;

[0022] Figure 7A This is a diagram showing the wettability of Sn and Ni. Figure 7B This is a diagram showing the wettability of Sn and BaTiO3;

[0023] Figures 8 to 11 This is a diagram illustrating a method of manufacturing a multilayer electronic component according to another embodiment of the present disclosure;

[0024] Figure 12 This is a diagram showing an image of a cross-section of a comparative example scanned using a scanning electron microscope (SEM);

[0025] Figure 13 This is a diagram showing an image of a cross-section of an example of the invention scanned using a scanning electron microscope (SEM); and

[0026] Figure 14 yes Figure 13 A magnified view of the interface between the internal electrode and the dielectric layer. Detailed Implementation

[0027] In the following description, embodiments of the present disclosure will be illustrated with reference to the accompanying drawings. However, the present disclosure may be exemplified in many different forms and should not be construed as limiting oneself to the specific embodiments set forth herein. Rather, these embodiments are provided so that the disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art. In the drawings, the shape and size of elements may be exaggerated for clarity. Furthermore, in the drawings, elements having the same function within the same scope of the inventive concept will be indicated by the same reference numerals.

[0028] In the accompanying drawings, irrelevant descriptions will be omitted for clarity of this disclosure, and thicknesses may be enlarged to clearly represent multiple layers and regions. The same reference numerals will be used to describe the same elements having the same function within the scope of the same concept. Throughout the specification, unless otherwise specifically stated, when a component is referred to as "comprising" or "including," it means that the component may also include other components, rather than excluding other components.

[0029] In the accompanying drawings, the first direction can be defined as the stacking direction or thickness direction T, the second direction can be defined as the length direction L, and the third direction can be defined as the width direction W.

[0030] Multilayer electronic components

[0031] Figure 1 A perspective view of a multilayer electronic assembly according to an embodiment of the present disclosure is shown schematically.

[0032] Figure 2 Schematic illustration along Figure 1 The cross-sectional view taken from line I-I'.

[0033] Figure 3 Schematic illustration along Figure 1 The cross-sectional view taken from line II-II'.

[0034] Figure 4 This is an exploded perspective view schematically illustrating a body having a stacked dielectric layer and internal electrodes according to an embodiment of the present disclosure.

[0035] Figure 5 It is shown Figure 2 The enlarged area P1 is shown in the diagram.

[0036] Figure 6 It is shown Figure 5 The enlarged area P2 is shown in the diagram.

[0037] In the following text, reference will be made to Figures 1 to 6 A multilayer electronic assembly according to embodiments of the present disclosure is described in detail.

[0038] According to an embodiment of the present disclosure, a multilayer electronic component 100 includes: a body 110 including a dielectric layer 111 and inner electrodes 121 and 122 alternately disposed with respect to the dielectric layer 111; and outer electrodes 131 and 132 disposed on the body and connected to the inner electrodes. A composite layer CL comprising Sn and Ni is disposed at the interface between the inner electrodes and the dielectric layer. The inner electrodes 121 and 122 include an interface portion IP adjacent to the composite layer CL and a central portion CP disposed between the interface portions. The interface portion IP includes a ceramic additive 23.

[0039] The body 110 is formed by alternately stacking dielectric layers 111 and internal electrodes 121 and 122.

[0040] The specific shape of the body 110 is not particularly limited, but as shown in the figure, the body 110 may have a hexahedral shape or a similar shape. Due to the shrinkage of the ceramic powder particles included in the body 110 during the sintering process, the body 110 may have a substantially hexahedral shape, rather than a hexahedral shape consisting of completely straight lines.

[0041] The main body 110 may have a first surface 1 and a second surface 2 that are opposite to each other in a first direction, a third surface 3 and a fourth surface 4 that are connected to the first surface 1 and the second surface 2 and are opposite to each other in a second direction, and a fifth surface 5 and a sixth surface 6 that are connected to the first surface 1 and the second surface 2, connected to the third surface 3 and the fourth surface 4 and are opposite to each other in a third direction.

[0042] The multiple dielectric layers 111 forming the body 110 may be in a sintered state, and adjacent dielectric layers 111 may be integrated to the extent that the boundaries between them are difficult to confirm without the use of a scanning electron microscope (SEM).

[0043] According to embodiments of this disclosure, the raw materials used to form the dielectric layer 111 are not particularly limited, as long as sufficient capacitance can be obtained. For example, barium titanate-based materials, lead-based perovskite composite materials, strontium titanate-based materials, etc., can be used. Barium titanate-based materials may include BaTiO3-based ceramic powder particles, and examples of ceramic powder particles may include BaTiO3 or calcium (Ca), zirconium (Zr), etc., partially dissolved in BaTiO3 (Ba... 1-x Ca x TiO3, Ba(Ti 1-y Ca y O3、(Ba 1-x Ca x (Ti) 1-y Zr y O3, Ba(Ti) 1-y Zr y O3, etc.

[0044] For the purposes of this disclosure, various ceramic additives, organic solvents, binders, dispersants, etc., can be added to powder particles such as barium titanate (BaTiO3) as materials for forming dielectric layer 111.

[0045] Furthermore, there are no particular restrictions on the thickness td of the dielectric layer 111.

[0046] However, reliability may be compromised when the dielectric layer is formed to a thickness of less than 0.6 μm, and in particular when the dielectric layer thickness is less than or equal to 0.41 μm.

[0047] As described below, according to embodiments of this disclosure, since the internal electrode connectivity and smoothness can be improved while maximizing the shrinkage of the internal electrode in the thickness direction to make the internal electrode thinner, reliability can be effectively improved even when the dielectric layer is very thin. Therefore, sufficient reliability can be ensured even when the thickness of the dielectric layer is less than or equal to 0.41 μm.

[0048] Therefore, when the thickness of dielectric layer 111 is less than or equal to 0.41 μm, the effect of improving reliability according to this disclosure can be significantly improved.

[0049] The thickness td of dielectric layer 111 can represent the average thickness of dielectric layer 111 disposed between the first inner electrode 121 and the second inner electrode 122.

[0050] The average thickness of dielectric layer 111 can be measured by scanning images of cross-sections of the subject in the length and thickness directions (LT direction) using a scanning electron microscope (SEM).

[0051] For example, regarding any dielectric layer 111 extracted from an image obtained by scanning a cross-section in the width direction of the central portion of the body 110 in both the length and thickness directions (LT direction) using a scanning electron microscope (SEM), its average thickness can be measured by measuring its thickness at 30 equally spaced points in the length direction.

[0052] The thickness can be measured at 30 equally spaced points at capacitor forming section A, which represents the area where inner electrodes 121 and 122 overlap each other.

[0053] The main body 110 may include a capacitor forming portion A and covering portions 112 and 113 formed on the upper and lower parts of the capacitor forming portion A. The capacitor forming portion A is disposed in the main body 110 and includes a first inner electrode 121 and a second inner electrode 122 disposed opposite to each other. A dielectric layer 111 is disposed between the first inner electrode 121 and the second inner electrode 122, and a capacitor is formed in the capacitor forming portion A.

[0054] In addition, the capacitor forming part A is the part that contributes to the capacitor forming, and it can be formed by repeatedly stacking multiple first inner electrodes 121 and second inner electrodes 122, and the dielectric layer 111 is located between the first inner electrodes 121 and the second inner electrodes 122.

[0055] The upper cover portion 112 and the lower cover portion 113 can be formed by stacking a single dielectric layer or two or more dielectric layers on the upper and lower surfaces in the thickness direction of the capacitor forming portion A, respectively, and the upper cover portion 112 and the lower cover portion 113 can be used to substantially prevent damage to the inner electrode due to physical stress or chemical stress.

[0056] The upper cover 112 and the lower cover 113 may not include the inner electrode and may include the same material as the dielectric layer 111.

[0057] In other words, the upper cover 112 and the lower cover 113 may include ceramic materials, such as barium titanate (BaTiO3) based ceramic materials.

[0058] Furthermore, the thickness of the covers 112 and 113 does not need to be particularly limited. However, the thickness tp of the covers 112 and 113 can be less than or equal to 20 μm to more easily achieve miniaturization and high capacitance of multilayer electronic components.

[0059] Additionally, edge portions 114 and 115 may be provided on the side surface of capacitor forming portion A.

[0060] Edge portions 114 and 115 may include an edge portion 114 disposed on the sixth surface 6 of the body 110 and an edge portion 115 disposed on the fifth surface 5 of the body 110. That is, edge portions 114 and 115 may be disposed on two side surfaces of the body 110 in the width direction.

[0061] like Figure 3 As shown, the edges 114 and 115 may represent the region between the two ends of the first inner electrode 121 and the second inner electrode 122 and the interface of the body 110 in a cross section taken along the width-thickness (WT) direction of the body 110.

[0062] Edges 114 and 115 can be used to prevent damage to the inner electrode due to physical or chemical stress.

[0063] Edge portions 114 and 115 can be formed by applying a conductive paste for forming the inner electrode (i.e., the paste for the inner electrode described below) to the area of ​​the ceramic green sheet other than the area where the edge portions will be formed.

[0064] In addition, in order to suppress the stepped portions of the inner electrodes 121 and 122, after the inner electrodes are cut to expose the fifth surface 5 and the sixth surface 6 of the laminated body, the edge portions 114 and 115 can also be formed by stacking a single dielectric layer or two or more dielectric layers on the two side surfaces of the capacitor forming portion A in the width direction.

[0065] The inner electrodes 121 and 122 may be alternately disposed with the dielectric layer 111.

[0066] The inner electrodes 121 and 122 may include a first inner electrode 121 and a second inner electrode 122. The first inner electrode 121 and the second inner electrode 122 may be alternately arranged opposite each other and a dielectric layer 111 is disposed between the first inner electrode 121 and the second inner electrode 122, and the first inner electrode 121 and the second inner electrode 122 may be exposed on the third surface 3 and the fourth surface 4 of the body 110, respectively.

[0067] Reference Figure 2 The first inner electrode 121 may be spaced apart from the fourth surface 4 and exposed through the third surface 3, and the second inner electrode 122 may be spaced apart from the third surface 3 and exposed through the fourth surface 4.

[0068] In this case, the first inner electrode 121 and the second inner electrode 122 can be electrically separated from each other by the dielectric layer 111 disposed between them.

[0069] Reference Figure 4 The main body 110 can be formed by alternately stacking ceramic green sheets printed with a first internal electrode 121 and ceramic green sheets printed with a second internal electrode 122, and then sintering them.

[0070] Reference Figure 6 A composite layer CL containing Sn and Ni can be disposed at the interface between the inner electrodes 121 and 122 and the dielectric layer 111. The inner electrodes 121 and 122 may include an interface portion IP adjacent to the composite layer CL and a central portion CP disposed between the interface portions. The interface portion IP may include a ceramic additive 23.

[0071] A conventional method for thinning the inner electrodes 121 and 122 involves printing a relatively thin conductive paste to form the inner electrodes and then sintering it. However, this method suffers from the potential for electrode breakage due to shrinkage in all directions during sintering, and also results in a deterioration in the smoothness of the inner electrodes.

[0072] In this disclosure, by controlling the shrinkage behavior during sintering, the internal electrode's connectivity and smoothness can be improved while simultaneously thinning the internal electrode.

[0073] During sintering, shrinkage typically occurs in the first, second, and third directions, ranging from 15% to 25%. However, in this disclosure, by maximizing the shrinkage of the inner electrode in the first direction (thickness direction) and suppressing its shrinkage in the second and / or third directions (length and / or width directions) during sintering, the inner electrode's connectivity and smoothness can be improved while thinning the inner electrode.

[0074] Figure 7A This is a diagram showing the wettability of Sn and Ni. Figure 7B This is a diagram showing the wettability of Sn and BaTiO3. (Refer to...) Figure 7A and Figure 7B It can be seen that Sn and Ni have high wettability (contact angle θ1 is less than or equal to 90 degrees), while Sn and BaTiO3 have low wettability (contact angle θ2 is greater than 90 degrees). Since the composite layer CL containing Sn and Ni has low wettability with the ceramic additive 23, the composite layer CL can act as a barrier to inhibit the movement of the ceramic additive 23 towards the dielectric layer 111, thus confining the ceramic additive 23 within the interface IP.

[0075] Ceramic additive 23 is confined within the interface portion IP to suppress sintering shrinkage in the transverse direction, and the central portion CP is constrained by the interface portion IP to induce enhanced shrinkage in the thickness direction. Therefore, the internal electrode connectivity and smoothness can be improved while simultaneously thinning the internal electrode.

[0076] In an embodiment, the interface portion IP can be a region extending from the interface between the composite layer CL and the inner electrodes 121 and 122 to a depth of 1 / 3 of the thickness of the inner electrodes.

[0077] In other words, when the internal electrode is divided into three parts in the first direction, it can have a central part CP disposed between the interface parts IP.

[0078] In addition, the interface IP may include 5% to 15% of ceramic additive 23.

[0079] When the ceramic additive 23 at the interface IP is less than 5% by area, the effect of the ceramic additive 23 in suppressing sintering shrinkage in the transverse direction may be insufficient. Furthermore, when the ceramic additive exceeds 15% by area, the ceramic additive content is too high, which may be quite detrimental to the thinning of the internal electrode.

[0080] Regarding any five inner electrodes extracted from images obtained by scanning a scanning electron microscope (SEM) of the central portion of the body 110 in the third direction (width direction) in the first and second directions (thickness and length directions), the area % of the ceramic additive included in the interface portion IP can be calculated by measuring the area occupied by the ceramic additive in up to 1 / 3 of the thickness of the inner electrode.

[0081] The central portion CP may also include some ceramic additives, but the amount of ceramic additives included in the central portion CP may be less than that included in the interface portion IP. In one example, the area occupied by ceramic additives per unit area of ​​the central portion CP may be less than the area occupied by ceramic additives per unit area of ​​the interface portion IP. Optionally, ceramic additives may not be included in the central portion CP.

[0082] Regarding a specific example, the area % of the ceramic additive in the central portion CP can be less than or equal to half the area % of the ceramic additive 23 in the interface portion IP. Additionally, the area % of the ceramic additive in the central portion CP can be less than 5% of the area.

[0083] In an embodiment, the Sn concentration of the composite layer CL may be greater than or equal to 5 times the Sn concentration of the central portion CP.

[0084] This is because when the Sn concentration of the composite layer CL is less than 5 times the Sn concentration of the central part CP, the effect of the ceramic additive 23 being bound in the interface part IP may be insufficient.

[0085] For example, any five inner electrodes extracted from an image obtained by scanning the central portion of the main body 110 in the third direction (width direction) using a scanning electron microscope (SEM) in the first and second directions (thickness and length directions) can be analyzed by energy-dispersive X-ray spectroscopy (EDS) line scanning along the thickness direction of the inner electrodes. The Sn concentration of the central portion CP and the Sn concentration of the composite layer CL can be measured, and the average value can be measured.

[0086] In one embodiment, the composite layer CL may comprise Sn and Ni in the form of Ni3Sn.

[0087] The Ni3Sn included in the composite layer CL can be identified by analyzing the interface between the inner electrodes 121 and 122 and the dielectric layer 111 through selected area difference (SAD) pattern analysis.

[0088] In one embodiment, the ceramic additive 23 included in the interface IP may be BaTiO3.

[0089] Because BaTiO3 has high wettability with Sn, it can more significantly improve the effect of suppressing the migration of ceramic additive 23 to dielectric layer 111 through the composite layer CL including Ni and Sn.

[0090] In this embodiment, the inner electrodes 121 and 122 may contain Ni as the main component. The Sn contained in the inner electrodes 121 and 122 melts at a temperature of 232°C or higher and migrates to the interface to form a Ni-Sn intermetallic compound. Additionally, the inner electrodes 121 and 122 may contain Ni as the main component, and may also contain one or more of copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0091] In one embodiment, the thickness of the composite layer CL can be from 10 nm to 30 nm. For example, the average thickness of the composite layer CL can be from 10 nm to 30 nm.

[0092] When the thickness of the composite layer CL is less than 10 nm, its barrier function may be insufficient. When its thickness exceeds 30 nm, delamination defects may occur due to premature sintering shrinkage.

[0093] Furthermore, the thickness te of the inner electrodes 121 and 122 does not need to be particularly limited.

[0094] However, typically, when the inner electrodes 121 and 122 are formed with a thickness of less than 0.6 μm, and particularly when the thickness of the inner electrodes 121 and 122 is less than or equal to 0.41 μm, there is a problem of deterioration in the connectivity and smoothness of the inner electrodes.

[0095] As described above, according to the embodiments of this disclosure, since the internal electrode connectivity and smoothness can be increased while maximizing the shrinkage of the internal electrode in the thickness direction to make the internal electrode thinner, excellent internal electrode connectivity and smoothness can be ensured even when the thickness of the internal electrodes 121 and 122 is 0.41 μm.

[0096] Therefore, when the thickness of the inner electrodes 121 and 122 is less than or equal to 0.41 μm, the effect according to this disclosure can be improved more significantly, and the miniaturization and high capacitance of the capacitor assembly can be achieved more easily.

[0097] The thickness te of the inner electrodes 121 and 122 can represent the average thickness of the inner electrodes 121 and 122.

[0098] The average thickness of the inner electrodes 121 and 122 can be measured by scanning the cross-section of the body in the length direction and thickness direction (second direction - first direction) using a scanning electron microscope (SEM).

[0099] For example, the average value of arbitrary inner electrodes 121 and 122 extracted from the cross-section of the main body 110 taken from the central portion in the width direction using a scanning electron microscope (SEM) can be measured by measuring the thickness at 30 equally spaced points in the length direction.

[0100] In one embodiment, the internal electrode connectivity of internal electrodes 121 and 122 may be greater than or equal to 85%.

[0101] Internal electrode connectivity can be defined as the ratio of the length of the portion that actually forms the internal electrode to the total length of the internal electrode.

[0102] For example, if the total electrode length measured at any point on the inner electrode 121 is defined as b, and the actual lengths of the portions forming the inner electrode are e1, e2, e3, and e4, then the inner electrode connectivity can be expressed as e / b, which is the value obtained by dividing the sum of the actual lengths of the inner electrodes (e = e1 + e2 + e3 + e4) by the total electrode length b.

[0103] When the internal electrode connectivity is less than 85%, it may be difficult to ensure sufficient capacitance.

[0104] According to embodiments of this disclosure, since the inner electrode can be thinned by maximizing the shrinkage of the inner electrode in the thickness direction, the inner electrode connectivity can be improved, ensuring that the inner electrode connectivity is greater than or equal to 85%.

[0105] There is no need to specifically limit the upper limit of the internal electrode connectivity, but considering manufacturing processes, the upper limit can be 97%.

[0106] External electrodes 131 and 132 are disposed on the main body 110 and connected to internal electrodes 121 and 122.

[0107] like Figure 2 As shown, the outer electrodes 131 and 132 may be disposed on the third surface 3 and the fourth surface 4 of the body 110, respectively, and may include the first outer electrode 131 and the second outer electrode 132 connected to the first inner electrode 121 and the second inner electrode 122, respectively.

[0108] In this embodiment, a multilayer electronic component 100 is described having a structure with two external electrodes 131 and 132, but the number or shape of the external electrodes 131 and 132 may be changed depending on the shape of the internal electrodes 121 and 122 or for any other purpose.

[0109] Furthermore, the outer electrodes 131 and 132 can be formed from any material such as metal, as long as they are conductive, and the specific material can be determined by taking into account electrical properties and structural stability, and the outer electrodes 131 and 132 can have a multilayer structure.

[0110] For example, external electrodes 131 and 132 may include: electrode layers 131a and 132a disposed on the body 110; and plating layers 131b and 132b formed on electrode layers 131a and 132a.

[0111] For a more specific example of electrode layers 131a and 132a, electrode layers 131a and 132a may be sintered electrodes comprising conductive metal and glass, or resin-based electrodes comprising conductive metal and resin.

[0112] Furthermore, electrode layers 131a and 132a may have a form in which a sintered electrode and a resin-based electrode are sequentially formed on the body. Additionally, electrode layers 131a and 132a can be formed by transferring a sheet including a conductive metal onto the body, or by transferring a sheet including a conductive metal onto a sintered electrode.

[0113] Materials with excellent electrical conductivity can be used as conductive metals included in electrode layers 131a and 132a, and there are no particular limitations on such materials. For example, the conductive metal can be one or more of nickel (Ni), copper (Cu), and their alloys.

[0114] Platings 131b and 132b are used to improve mounting characteristics. There are no particular restrictions on the type of platings 131b and 132b; they can be one or more of Ni, Sn, Pd and their alloys, and can be formed using multiple layers.

[0115] Regarding more specific examples of plating layers 131b and 132b, plating layers 131b and 132b may be Ni plating layers or Sn plating layers, or may have the following forms: Ni plating layers and Sn plating layers are sequentially formed on electrode layers 131a and 132a, or Sn plating layers, Ni plating layers and Sn plating layers are sequentially formed. Furthermore, plating layers 131b and 132b may also include multiple Ni plating layers and / or multiple Sn plating layers.

[0116] The size of the multilayer electronic component 100 does not require special restrictions.

[0117] However, in order to achieve both miniaturization and high capacitance, the reliability improvement effect according to this disclosure can be more significantly improved in multilayer electronic components 100 with dimensions of 0402 (length × width of 0.4 mm × 0.2 mm) or smaller, since the number of stacked layers needs to be increased by reducing the thickness of the dielectric layer and the internal electrode.

[0118] Therefore, considering manufacturing errors and the dimensions of the external electrodes, the reliability improvement effect according to this disclosure can be more significantly improved when the length of the multilayer electronic component 100 is less than or equal to 0.44 mm and the width is less than or equal to 0.22 mm. Here, the length of the multilayer electronic component 100 may refer to the dimension of the multilayer electronic component 100 in the second direction, and the width of the multilayer electronic component 100 may refer to the dimension of the multilayer electronic component 100 in the third direction.

[0119] Methods for manufacturing multilayer electronic components

[0120] Figures 8 to 11 This is a diagram illustrating a method for manufacturing a multilayer electronic component according to another embodiment of the present disclosure.

[0121] In the following text, reference will be made to Figures 8 to 11 A method for manufacturing a multilayer electronic component according to another embodiment of the present disclosure is described.

[0122] According to another aspect of this disclosure, a method for manufacturing a multilayer electronic component includes the following operations: preparing a ceramic green sheet; applying a paste for an internal electrode onto the ceramic green sheet to form an internal electrode pattern; stacking the ceramic green sheets with the internal electrode pattern to form a laminate; first firing the laminate; second firing the first-fired laminate; sintering the second-fired laminate to form a body including a dielectric layer and an internal electrode; and forming an external electrode on the body. The paste for the internal electrode includes Sn powder particles 22, ceramic additives 23, and conductive powder particles 21, and the conductive powder particles 21 have a core-shell 21b structure, wherein the core 21a contains Ni, and the shell 21b contains Ni, S, and O.

[0123] Operation of preparing ceramic green sheets

[0124] First, a ceramic green sheet is prepared for forming the dielectric layer 111.

[0125] Ceramic green sheets are used to form the dielectric layer 111 of the body 110, and a slurry can be prepared by mixing ceramic powder particles 11, polymers, and solvents. The ceramic green sheets can be formed by shaping the slurry into a sheet shape with a predetermined thickness using a doctor blade.

[0126] Operation of forming internal electrode pattern

[0127] Subsequently, an internal electrode is formed on at least one surface of each of the ceramic green sheets by printing a conductive paste for the internal electrode onto a predetermined thickness. Screen printing or gravure printing can be used as the printing method for the conductive paste for the internal electrode.

[0128] The paste used for the internal electrode may include Sn powder particles, ceramic additives, and conductive powder particles. The conductive powder particles have a core-shell structure, with the core containing Ni and the shell containing Ni, S, and O. Because the internal electrode is formed using the paste for the internal electrode, shrinkage of the internal electrode in the first direction (thickness direction) during sintering can be maximized, and shrinkage of the internal electrode in the second and third directions (length and width directions) can be suppressed. This allows for improved internal electrode connectivity and smoothness while simultaneously thinning the internal electrode. Furthermore, the internal electrode structure of the multilayer electronic assembly according to the embodiments of this disclosure can be implemented more easily.

[0129] Figure 8 A conductive paste for an internal electrode, comprising Sn powder particles 22, ceramic additives 23, and conductive powder particles 21, is shown printed on a ceramic green sheet comprising ceramic powder particles 11. The conductive powder particles 21 have a core-shell structure 21a-21b, wherein the core 21a contains Ni and the shell 21b contains Ni, S, and O.

[0130] The Ni, S and O contained in shell 21b can be used to delay the shrinkage of Ni at low temperatures.

[0131] When the shell has a Ni-O structure that does not contain sulfur, it is difficult to delay the shrinkage of Ni because the surface O reacts with C to produce CO, CO2, etc. at the beginning of the second firing.

[0132] On the other hand, according to this disclosure, when the shell 21b contains Ni, S, and O, the S and O are firmly bonded together to maintain the oxide film at the start of the secondary firing, thereby delaying the shrinkage of Ni. Furthermore, by delaying the agglomeration or necking between Ni particles, a path is provided for the ceramic additive 23 to move through to the interface of the inner electrode.

[0133] In the embodiments, the average size of the conductive powder particles may be less than 100 nm, and the ceramic additive may have an average size of 5 nm to 10 nm.

[0134] To form thin internal electrodes, it is advantageous to use fine-grained conductive powder particles. With generally fine-grained conductive powder particles, the sintering shrinkage initiation temperature can be shifted to a lower temperature, and the difference in sintering initiation temperature between the generally fine-grained conductive powder particles and the dielectric layer may increase, potentially leading to defects such as delamination.

[0135] However, the Ni, S and O contained in the shell 21b of the conductive powder particle 21 according to this disclosure can be used to delay the shrinkage of Ni at low temperatures, so that defects such as delamination can be suppressed even when fine powder particles smaller than 100 nm are used.

[0136] In one embodiment, in the core-shell structure, the shell 21b may contain 1000 ppm to 2000 ppm of S.

[0137] As conductive powder particles become finer, higher sulfur (S) concentrations are required to achieve sufficient shrinkage delay. For conductive powder particles with an average particle size of 100 nm or less, a shrinkage delay effect can be sufficient when coated with 1000 ppm or more of S, and if the S concentration exceeds 2000 ppm, the shrinkage delay effect may not be significantly different.

[0138] In one embodiment, Ni-O may be disposed on the surface of the shell 21b. When nanoscale metal powder particles are exposed to the atmosphere, an exothermic reaction occurs through their reaction with oxygen; Ni-O may be disposed on the surface of the shell 21b to prevent the exothermic reaction from occurring.

[0139] In one embodiment, Sn powder particles 22 may be 0.3 wt% to 1.0 wt% compared to 100 wt% conductive powder particles 21. If Sn powder particles 22 are less than 0.3 wt%, it may be insufficient to form the composite layer CL with a thickness greater than or equal to 10 nm, and if Sn powder particles 22 exceed 1.0 wt%, the composite layer CL may be over-formed with a thickness greater than or equal to 30 nm. Accelerated sintering shrinkage may lead to delamination defects.

[0140] In one embodiment, the ceramic additive 23 can be 5 wt% to 20 wt% compared to 100 wt% of conductive powder particles 21. When conductive powder particles with an average particle size less than or equal to 100 nm are used as the main component of the inner electrodes 121 and 122, a ceramic additive content greater than or equal to 5 wt% is required compared to 100 wt% of conductive powder particles, and a higher content of ceramic additive is required as the average particle size decreases to suppress sintering shrinkage. When the proportion of ceramic additive exceeds 20 wt% compared to 100 wt% of conductive powder particles, it may be detrimental to making the inner electrodes thinner.

[0141] In one embodiment, ceramic additive 23 may be BaTiO3.

[0142] Because BaTiO3 has high wettability with Sn, the effect of suppressing the migration of ceramic additive 23 to ceramic green sheets by the composite layer CL containing Ni and Sn can be more significant.

[0143] Operations to form a stack

[0144] A laminate is formed by stacking ceramic green sheets with internal electrode patterns. The laminate can be pressed and pressure applied in the stacking direction (first direction).

[0145] In this case, the stack can be cut into blanks by cutting each region corresponding to the body of a multilayer electronic component. Furthermore, one end of the internal electrode pattern can be cut to alternately expose two end surfaces in a second direction.

[0146] First firing operation

[0147] After this, the initial firing of the laminated body can be performed.

[0148] Reference Figure 9 In the initial firing operation, Sn powder particles 22 with low melting point move to the interface with the ceramic green sheet in liquid form, and because Sn has low wettability with ceramic powder particles 11, Sn is disposed at the interface in a layer shape 22'.

[0149] In one embodiment, the initial firing operation can be performed at a temperature of 250°C to 350°C in a strongly reducing atmosphere. Within this temperature range, the Sn powder particles can be in liquid form, and because Sn has high oxidizing reactivity, oxidation of Sn can be prevented by heat treatment in a strongly reducing atmosphere.

[0150] In this case, the strong reducing atmosphere used to prevent Sn oxidation can be a gas atmosphere mixed with nitrogen (N2) gas and hydrogen (H2) gas. Based on 100% by volume of the total nitrogen gas and hydrogen gas, the strong reducing atmosphere has 0.2% to 1.0% by volume of hydrogen gas.

[0151] Secondary firing operation

[0152] After that, a second firing of the laminated body that was fired in the first firing can be performed.

[0153] When the shell 21b of the conductive powder particles 21 contains Ni, S, and O, the shrinkage of Ni can be delayed because the oxide film can be maintained at the beginning of the secondary firing stage, since the S and O are firmly bonded. In addition, by delaying the agglomeration or necking between Ni particles, a path can be provided for the ceramic additive 23 to move to the interface of the inner electrode.

[0154] Figure 10 This is a schematic diagram showing the state after the second firing is completed. (Refer to...) Figure 10 At the interface with the ceramic green sheet, the Sn layer and Ni particles react to form a composite layer CL containing Sn and Ni, and the ceramic additive 23 moves to the interface between the inner electrode and the composite layer CL. Since the composite layer CL containing Sn and Ni has low wettability with the ceramic additive, it can prevent the ceramic additive 23 from moving towards the ceramic green sheet and acts as a barrier to bind the ceramic additive 23 at the interface IP.

[0155] In one embodiment, the secondary firing operation can be performed at 600°C to 900°C. Within this temperature range, the formation of the composite layer CL containing Sn and Ni and the migration of the ceramic additive 23 can be promoted.

[0156] Sintering operation

[0157] Subsequently, the laminated body that has been sintered twice can be sintered to form a body including a dielectric layer and an internal electrode.

[0158] Reference Figure 11The ceramic additive 23 is confined within the interface portion IP to suppress sintering shrinkage in the transverse direction, and the central portion CP is constrained by the interface portion IP to induce enhanced shrinkage in the thickness direction. Therefore, the internal electrode's connectivity and smoothness can be improved while simultaneously thinning the internal electrode. Additionally, sintered ceramic powder particles 11 are used to form a dielectric layer 111.

[0159] In this embodiment, the sintering process can be performed in a reducing atmosphere. Alternatively, the sintering process can be performed by adjusting the heating rate, but is not limited thereto; the heating rate can be from 30°C / 60s to 50°C / 60s at 700°C or lower, and the sintering temperature can be from 900°C to 1300°C.

[0160] Operation of forming external electrodes

[0161] After that, the operation of forming an external electrode on the main body can be performed.

[0162] In this case, the exposed portions of the first inner electrode 121 and the second inner electrode 122 exposed to the two end surfaces of the body in the second direction can be covered to form a first outer electrode 131 electrically connected to the first inner electrode and a second outer electrode 132 electrically connected to the second inner electrode.

[0163] Additionally, if necessary, the surfaces of the first external electrode 131 and the second external electrode 132 may be plated with nickel, tin, or palladium.

[0164] (Example)

[0165] After forming a laminate by stacking ceramic green sheets with conductive paste printed on them for the inner electrodes, a primary firing operation, a secondary firing operation, and a sintering operation are performed to form the outer electrodes, thereby preparing sample sheets for the inventive examples and comparative examples. In the inventive examples and comparative examples, other conditions besides the conductive paste for the inner electrodes can be applied in the same manner.

[0166] In the comparative example, a conductive paste for the internal electrode was used, comprising Ni powder particles with an average size of 60 nm and BaTiO3 powder particles with an average size of 10 nm as a ceramic additive.

[0167] In the example of the invention, a conductive paste for an internal electrode is used, comprising conductive powder particles with a core-shell structure, a ceramic additive, and Sn powder particles. The core comprises Ni, and the shell comprises Ni, S, and O. The average size of the conductive powder particles is 60 nm, the average size of the ceramic additive is 10 nm, and the average size of the Sn powder particles is 60 nm. 1 wt% of Sn powder particles are added compared to 100 wt% of the conductive powder particles. Furthermore, the ceramic additive is BaTiO3.

[0168] Compare Figure 12 (Comparison example) and Figure 13 (Example of the invention), in Figure 12 and Figure 13 The cross-section of the sample sheet taken from the center of the sample sheet along the first and second directions was scanned using a scanning electron microscope (SEM). Compared with the comparative example, in the case of the inventive example, a significant improvement in the smoothness of the internal electrode can be seen.

[0169] Furthermore, in the cross-sectional image, the length of the portion actually forming the inner electrode is measured relative to the total length of all inner electrodes, and the electrode connectivity of each inner electrode is obtained, then an average value is calculated. This confirms that the inner electrode connectivity is 93% in the inventive example and 84% in the comparative example, demonstrating a 9% improvement in inner electrode connectivity.

[0170] Furthermore, compared to the comparative example, the average thickness of the internal electrode in the invention example is reduced by 5.8%.

[0171] Reference will Figure 13 The magnified interface between the internal electrode and the dielectric layer in the middle Figure 14 It can be confirmed that a composite layer containing Ni and Sn is disposed at the interface between the dielectric layer and the inner electrode, and the common material (ceramic additive of the inner electrode) is bound at the interface of the inner electrode.

[0172] Regarding five arbitrary inner electrodes extracted from images obtained by scanning cross-sections taken at the central portion of the main body of the invention example in the third direction (width direction) in the first and second directions (thickness and length directions), the area occupied by ceramic additives in a region (interface portion) with a depth of 1 / 3 of the inner electrode thickness is measured, and each value and their average value are described in Table 1 below.

[0173] [Table 1]

[0174] 1 6.5 2 5.1 3 14.9 4 8.8 5 12.5 average value 9.6

[0175] As can be seen from Table 1, in the case of the invention example, the interface IP may include 5% to 15% of ceramic additive 23.

[0176] Five arbitrary inner electrodes were extracted from images obtained by scanning an electron microscope (SEM) of the central portion of the body 110 in the third direction (width direction) along the first and second directions (thickness and length directions). Energy dispersive X-ray spectroscopy (EDS) line scan analysis was performed along the thickness direction of the inner electrodes, and the ratio of Sn concentration in the composite layer CL to Sn concentration in the central portion CP was measured. Each value and their average value are shown in Table 2 below.

[0177] [Table 2]

[0178] 1 5.1 2 6.4 3 5.8 4 5.4 5 5.7 average value 5.7

[0179] Referring to Table 2, it can be seen that the Sn concentration of the composite layer CL is greater than or equal to 5 times the Sn concentration of the central CP.

[0180] As described above, according to embodiments of the present disclosure, as one of the various effects of the present disclosure, the reliability of multilayer electronic components can be improved.

[0181] One of the various effects of this disclosure is to maximize the shrinkage of the inner electrode in the thickness direction and suppress its shrinkage in the length and width directions, thereby making the inner electrode thinner and improving the connectivity and smoothness of the inner electrode.

[0182] While exemplary embodiments have been shown and described above, it will be readily understood by those skilled in the art that modifications and variations may be made without departing from the scope of the invention as defined by the appended claims.

Claims

1. A multilayer electronic component, comprising: The main body includes a dielectric layer and internal electrodes alternately disposed with the dielectric layer; as well as An external electrode is disposed on the main body and connected to the internal electrode. The composite layer containing Sn and Ni is disposed at the interface between the inner electrode and the dielectric layer. The inner electrode includes a central portion and an interface portion between the composite layer and the central portion of the inner electrode, wherein the interface portion includes a ceramic additive. The Sn concentration in the composite layer is greater than or equal to five times the Sn concentration in the central part.

2. The multilayer electronic component according to claim 1, wherein, The interface portion is the region extending from the interface between the composite layer and the inner electrode to a depth of 1 / 3 of the thickness of the inner electrode.

3. The multilayer electronic component according to claim 1, wherein, The ceramic additive accounts for 5% to 15% of the area of ​​the interface.

4. The multilayer electronic component according to claim 1, wherein, The area percentage of the ceramic additive in the central portion is less than or equal to 1 / 2 of the area percentage of the ceramic additive in the interface portion.

5. The multilayer electronic component according to claim 1, wherein, The internal electrode connectivity is less than or equal to 97%, and the internal electrode connectivity is the ratio of the length of the portion that actually forms the internal electrode to the total length of the internal electrode.

6. The multilayer electronic assembly according to claim 1, wherein, The composite layer contains Sn and Ni in the form of Ni3Sn.

7. The multilayer electronic assembly according to claim 1, wherein, The ceramic additive includes BaTiO3.

8. The multilayer electronic component according to claim 1, wherein, The internal electrode contains Ni as its main component.

9. The multilayer electronic component according to claim 1, wherein, The average thickness of the composite layer is 10 nm to 30 nm.

10. The multilayer electronic assembly according to claim 1, wherein, The average thickness of the internal electrode is less than or equal to 0.41 μm.

11. The multilayer electronic assembly according to claim 1, wherein, The average thickness of the dielectric layer is less than or equal to 0.41 μm.

12. The multilayer electronic assembly according to claim 1, wherein, The internal electrode connectivity is greater than or equal to 85%, and the internal electrode connectivity is the ratio of the length of the portion that actually forms the internal electrode to the total length of the internal electrode.

13. A method for manufacturing a multilayer electronic component, comprising the following operations: Preparation of ceramic green sheets; A paste for the internal electrode is applied to the ceramic green sheet to form an internal electrode pattern; A laminate is formed by stacking the ceramic green sheets having the internal electrode pattern. The laminated body is first fired; A layered body that has been fired twice and then fired once; Sintering a laminated body that has undergone secondary firing to form a bulk material including a dielectric layer and internal electrodes; and An external electrode is formed on the main body. The paste used for the internal electrode comprises Sn powder particles, ceramic additives, and conductive powder particles. The conductive powder particles have a core-shell structure, wherein the core contains Ni and the shell contains Ni, S and O.

14. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The average size of the conductive powder particles is less than 100 nm.

15. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The shell contains 1000 ppm to 2000 ppm of S.

16. The method for manufacturing a multilayer electronic component according to claim 13, wherein, Ni-O is disposed on the surface of the shell.

17. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The Sn powder particles are 0.3 wt% to 1.0 wt% compared to 100 wt% of the conductive powder particles.

18. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The ceramic additive is 5 wt% to 20 wt% compared to 100 wt% of the conductive powder particles.

19. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The ceramic additive includes BaTiO3.

20. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The initial firing operation is carried out at a temperature of 250°C to 350°C in a reducing atmosphere.

21. The method for manufacturing a multilayer electronic component according to claim 20, wherein, The reducing atmosphere is a gaseous atmosphere containing a mixture of nitrogen and hydrogen gases, and based on 100% by volume of the total nitrogen and hydrogen gases, the reducing atmosphere contains 0.2% to 1.0% by volume of hydrogen gas.

22. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The secondary firing operation is performed at a temperature of 600°C to 900°C.

23. The method for manufacturing a multilayer electronic component according to claim 13, wherein, The sintering operation is performed at a temperature of 900°C to 1300°C.

24. A multilayer electronic component, comprising: The main body includes a dielectric layer and internal electrodes alternately disposed with the dielectric layer; as well as An external electrode is disposed on the main body and connected to the internal electrode. The inner electrode includes a central portion and an interface portion spaced apart from the dielectric layer and including a ceramic additive. The interface portion is disposed between the dielectric layer and the central portion of the inner electrode. The area percentage of the ceramic additive in the interface portion of the internal electrode is greater than the area percentage of the ceramic additive in the central portion, and The ceramic additive accounts for 5% to 15% of the area of ​​the interface.

25. The multilayer electronic assembly according to claim 24, wherein, The ceramic additive includes BaTiO3.

26. The multilayer electronic assembly according to claim 24, wherein, The internal electrode contains Ni as its main component.

27. The multilayer electronic assembly according to claim 24, wherein, The area percentage of the ceramic additive in the central portion is less than or equal to 1 / 2 of the area percentage of the ceramic additive in the interface portion.

28. The multilayer electronic assembly according to claim 24, wherein, The average thickness of the internal electrode is less than or equal to 0.41 μm.

29. The multilayer electronic assembly according to claim 24, wherein, The average thickness of the dielectric layer is less than or equal to 0.41 μm.

30. The multilayer electronic assembly according to claim 24, wherein, The internal electrode connectivity is greater than or equal to 85%, and the internal electrode connectivity is the ratio of the length of the portion that actually forms the internal electrode to the total length of the internal electrode.

Citation Information

Patent Citations

  • Multi-layered ceramic electronic component

    CN110838409A

  • Multilayer ceramic electronic component and method of manufacturing the same

    US20170186542A1